Best practice recommendations for implantable neuromodulation therapies for pain II: Intrathecal drug delivery systems; Peripheral nerve stimulation; Sacral neuromodulation - Preeti Doshi; Vijay Bhaskar Bandikatla; Krishna Poddar; Rajkumar Arora; Pravesh Kanthed; Samarjit Dey (Indian Journal of Pain, 2023)
This is a part II of the best practice recommendations for implantable neuromodulation therapies for pain. Part I has already covered Spinal cord stimulation (SCS). We shall be be covering Intrathecal drug delivery systems (IDDS), Peripheral nerve stimulation (PNS) and Sacral nerve neuromodulation (SNM) in this article. Chronic pain has a huge global prevalence of 20% and in a country like India which has been labeled by the UN as the most populous country in April 2023, the problem is likely to explode and pose a huge challenge to Indian Practitioners. In addition to this can also be due to an expected doubling of individuals over 65 years of age by rising aging population. Patients failing conservative medical management (CMM) can be benefited from advanced pain therapies, including neuromodulation. This is for the first time that practice recommendations are published to guide practitioners offering this treatment in India.This can also be a reference for selecting the most appropriate patients to optimize outcomes. This can also provide motivation to start collecting information in the local database and also to convince our reimbursement agencies about incorporating this useful modality in the gamut of approved pain interventions.